PERKAWINAN DI BAWAH UMUR DALAM HUKUM ADAT BALI DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - , Loresta Cahyaning Lintang, Rama Pramu Wicaksono (Fakultas Hukum Universitas Sebelas Maret, 2015)
AbstractOne indicator of a rule or law is said to be good with legal certainty. Law No. 1 of 1974 on Marriage is one form of unification of law which is a follow up of the existence of legal pluralism with a variety of customary law that developed in the community. Purpose of Marriage Act is to create a society that is the rule of law and legal certainty for the people who are bound by marriage with the diversity of culture and the existence of customary law are still inherent in the culture in Indonesia. Where problems in the Marriage Act contained in the validity of underage marriage in Article 7 paragraph (1) and paragraph (2) of the Act 1 of 1974 that